EFFECT OF SERVICE LEARNING AND EDUCATIONAL TRIPS INSTRUCTIONAL STRATEGIES ON PRIMARY SCHOOL PUPILS’ ENVIRONMENTAL LITERACY IN SOCIAL STUDIES IN OYO STATE, NIGERIA - Gbadamosi, Tolulope Victoria (PEOPLE: International Journal of Social Sciences, 2018)
The study, determined the effect of service learning and educational trips instructional strategies and moderating effect of school location and gender on primary school pupils’ environmental literacy in social studies. The pretest, posttest, control group, quasi-experimental design with a 3x2x2 factorial matrix was adopted. A total of two hundred and sixty-four primary 5 pupils were used from 12 primary schools purposively selected from four local government areas in Oyo town, Oyo State, Nigeria and randomly assigned to two experimental and control groups. The experimental groups I and II were treated with service learning and educational trips respectively while control group was exposed to conventional strategy, each group for 12 weeks. Instruments used were Environmental Knowledge Test (r=0.86), Environmental Attitude Scale (r= 0.77) and Environmental Practices Scale (r= 0.76). Seven hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance, Scheffé post hoc and graphs. Treatments had significant effects on pupils’ environmental knowledge (F (2; 251) =29.98; p < 0.05), attitude (F (2; 251) =3.57; p < 0.05) and practices (F (2; 251) = 12.93; p < 0.05). Gender had no significant effect on pupils’ environmental knowledge, attitude and practices. School location had significant effect on environmental practices (F (1; 251) = 75.80; p <0.05). The 2-way interaction effect of treatment and school location was significant on pupils’ environmental knowledge (F (2; 251) = 11.57; p< 0.05). Educational trips had a positive effect on promoting environmental knowledge and attitude of primary school pupils in Oyo Town. Service learning was more effective in enhancing environmental practices than conventional strategy. Therefore, the two strategies are recommended to be used in the teaching of environmental education components of primary school social studies.